2022
DOI: 10.1021/acs.jmedchem.1c02217
|View full text |Cite
|
Sign up to set email alerts
|

Pocket-to-Lead: Structure-Based De Novo Design of Novel Non-peptidic HIV-1 Protease Inhibitors Using the Ligand Binding Pocket as a Template

Abstract: A novel strategy for lead identification that we have dubbed the “Pocket-to-Lead” strategy is demonstrated using HIV-1 protease as a model target. Sometimes, it is difficult to obtain hit compounds because of the difficulties in satisfying the complex pharmacophoric features. In this study, a virtual fragment hit which does not match all of the pharmacophore features but has key interactions and vectors that could grow into remaining pharmacophore features was optimized in silico. The designed compound 9 demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Although compounds 1 and 2 with the basic scaffold did not show detectable binding activity against cannabinoid receptors, they formed considerable interactions with protein residues and served as good starting points for further structure-based optimization. Utilizing structure-based strategies, several other studies have also reported that high-affinity compounds can be developed by starting from weak or even false hits, forming key interactions with the binding pockets. This study illustrated the potential of reverse docking for exploring novel chemical spaces in drug discovery, thereby expanding its utility. Using the SBDD strategy, we expect to attempt various organometallic compounds with kinetically inert scaffolds in the CSD so that novel chemical space can be explored against different targets.…”
Section: Discussionmentioning
confidence: 81%
“…Although compounds 1 and 2 with the basic scaffold did not show detectable binding activity against cannabinoid receptors, they formed considerable interactions with protein residues and served as good starting points for further structure-based optimization. Utilizing structure-based strategies, several other studies have also reported that high-affinity compounds can be developed by starting from weak or even false hits, forming key interactions with the binding pockets. This study illustrated the potential of reverse docking for exploring novel chemical spaces in drug discovery, thereby expanding its utility. Using the SBDD strategy, we expect to attempt various organometallic compounds with kinetically inert scaffolds in the CSD so that novel chemical space can be explored against different targets.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the two entries (2 and 3) both used virtual screening for hit finding, similar to the protein kinase A example, thereby perhaps illustrating the growing understanding of the binding site for this class of enzymes. 12,13 Specifically, HIV-1 protease has been a pharmaceutical target for decades, and SARS CoV-2 Mpro has received massive Oversized composed float in tbl2 (504pt x 1227.5858pt) -Float Skipped attention, which has led to the rapid development of Paxlovid, a drug targeting this viral protease. 37,38 Enzymes (Other).…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…The HIV-1 protease (PDB ID: 7WCQ) was also selected for molecular docking and its crystal was also retrieved from the Protein Data Bank and used as the receptor protein. 47 Redocking has also been performed to validate our molecular docking protocols. Initially, the protein coordinates were prepared by deleting all the water and heteroatoms to make the targeted protein receptor-free.…”
Section: Computational Details Of Dft Calculationsmentioning
confidence: 99%